Flipped Classroom and Collaborative Learning Model and Its Effectiveness: Research and Development - Nugroho, Nugroho; Solihatin, Etin; Ibrahim, Nurdin (Universitas Negeri Semarang, 2024)
This research uses a qualitative approach. The research method used is research and development using a combination of development models from Borg & Gall and 4D Thiagarajan. This research aims to find out how the development, feasibility, and effectiveness of the learning model is being developed. This research uses a sample of students majoring in English. The feasibility test was carried out by three experts: design, media, and learning materials experts. The effectiveness test was carried out by comparing the results of the pre-test and post-test. This research shows that the model developed is suitable for application in learning. Apart from that, the results of the comparison of results show that the post-test value is 7.84 greater than the pre-test result. This shows that the model developed is effective. This research can be used as a reference for policymakers in higher education, and this learning model is feasible to implement. Further research can be carried out for courses with other development models.